Case report: Filarial infection of a parti-coloured bat: Litomosa sp. adult worms in abdominal cavity and microfilariae in bat semen - Pikula, Jiri; Piacek, Vladimir; Bandouchova, Hana; Bartlova, Marie; Bednarikova, Sarka; Burianova, Romana; Danek, Ondrej; Jedlicka, Petr; Masova, Sarka; Nemcova, Monika; Seidlova, Veronika; Zukalova, Katerina; et al. (Frontiers in Veterinary Science, 2023)
Background: Filarial infections have been understudied in bats. Likewise, little is known about pathogens associated with the reproductive system in chiropterans. While semen quality is critical for reproductive success, semen-borne pathogens may contribute to reproductive failure. Methods: For the first time we performed electroejaculation and used computer-assisted semen analysis to provide baseline data on semen quality in a parti-coloured bat (Vespertilio murinus). Results: The semen quality values measured in the V. murinus male appeared high (semen concentration = 305.4 x 106/mL; progressive and motile sperm = 46.58% and 60.27%, respectively). As an incidental finding, however, microfilariae were observed in the bat semen examined. At necropsy, eight adult filarial worms, later genetically identified as Litomosa sp., were found in the peritoneal cavity, close to the stomach, of the same particoloured bat male dying as a result of dysmicrobia and haemorrhagic gastroenteritis in a wildlife rescue centre. Histopathology revealed microfilariae in the testicular connective tissue and the epidydimal connective and fat tissues. A PCR assay targeting cytochrome c oxidase subunit 1 confirmed that adult worms from the peritoneal cavity and testicular microfilariae were of the same filarial species. Mildly engorged argasid mite larvae attached to the bat skin proved negative for filarial DNA and the adult filarial worms proved negative for endosymbiont Wolbachia. Conclusions: While the standard filarial life cycle pattern involves a vertebrate definitive host and an invertebrate vector, represented by a blood-sucking ectoparasite, our finding suggests that microfilariae of this nematode species may also be semen-borne, with transmission intensity promoted by the polygynous mating system of vespertilionid bats in which an infected male mates with many females during the autumn swarming. Presence of microfilariae may be expected to decrease semen quality and transmission via this route may challenge the success of reproductive events in females after mating. Further investigation will be necessary to better understand the bat-parasite interaction and the life cycle of this filarial worm.